2007
DOI: 10.2332/allergolint.o-06-453
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Japanese Cedar Pollinosis in an Artificial Exposure Chamber (OHIO Chamber)

Abstract: This is the first clinical study using Japanese cedar pollen under well-controlled conditions in the OHIO chamber in which the induction of allergic symptoms was observed. The OHIO chamber will be useful for studying allergic rhinitis in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…These numbers are equivalent to the range of 3,000–12,000 determined by the KC-20 leaser counter used in the OHIO Chamber system [11]. Based on these findings, the pollen dispersal concentrations used in this study (maximum of 12,000 grains/m 3 ) are considered to be valid and not too high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These numbers are equivalent to the range of 3,000–12,000 determined by the KC-20 leaser counter used in the OHIO Chamber system [11]. Based on these findings, the pollen dispersal concentrations used in this study (maximum of 12,000 grains/m 3 ) are considered to be valid and not too high.…”
Section: Discussionmentioning
confidence: 99%
“…The aerosol was diluted with the outside air and dispersed in the Chamber. Air flow generator systems aimed at circulating the indoor air were set in the four corners of the Chamber, which allowed even distribution of the pollen at the target pollen dispersal concentration in the Chamber [11]. The target pollen dispersal concentrations were determined by means of the laser particle counter KC-20 (Rion, Tokyo, Japan), which allows real-time determination of the pollen concentration on the basis of the scattered light of laser illuminant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashiguchi et al (53) reported that artificial exposure to Japanese cedar pollen at 2500 pollen grains/m 3 , which is equivalent to the airborne pollen amount in the early pollinating season, caused penetration of 250 and 14 grains/h to the nose and eyes in humans. Airborne pollen amount during the middle and late pollinating season is ϳ5000 pollen grains/m 3 (53) and it could be estimated to cause penetration of 500 grains/h to the nose, which is equivalent to 5 g of grains/h (13,54).…”
Section: Discussionmentioning
confidence: 99%
“…We also started basic studies in July 2004 with the aim of constructing a system that could enable simultaneous exposure of multiple subjects to JC pollen antigen under uniform conditions at any time of year. Thus, our artificial exposure chamber (OHIO Chamber) was constructed at Samoncho Clinic in Yotsuya at the centre of Tokyo [11].…”
Section: Introductionmentioning
confidence: 99%